2016
DOI: 10.1055/s-0035-1559790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Treatment on Serum Sclerostin Level

Abstract: Sclerostin is an osteocyte-secreted endogenous inhibitor of Wnt signaling. Several systemic and local factors have been suggested as possible regulators of sclerostin expression by osteocytes. In this study, we examined the effect of vitamin D treatment on sclerostin levels. 44 patients with diagnosis of vitamin D deficiency (25(OH)D≤20 ng/ml) were involved in the study. Patients had monthly intramuscular injection of 300.000 IU cholecalciferol for 3 consecutive months. Sclerostin, 25(OH)D, parathyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Inconsistently, Yadav et al showed that high dose vitamin D supplementation did not affect serum sclerostin levels in non-diabetic stage G3-4 CKD patients [27]. Furthermore, Acibucu et al demonstrated even a decrease in sclerostin level during intramuscular therapy with 300.000 IU cholecalciferol injected monthly for 3 consecutive months in vitamin D deficient non-CKD patients [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Inconsistently, Yadav et al showed that high dose vitamin D supplementation did not affect serum sclerostin levels in non-diabetic stage G3-4 CKD patients [27]. Furthermore, Acibucu et al demonstrated even a decrease in sclerostin level during intramuscular therapy with 300.000 IU cholecalciferol injected monthly for 3 consecutive months in vitamin D deficient non-CKD patients [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, using Saos-2 cells, Wijenayaka et al showed that 1α,25-dihydroxyvitamin D3 induces the expression of Sost/Sclerostin (57), whereas St John et al found that it decreases the transcriptional activity of the Sost promoter (52). Similarly conflicting clinical data on the effects of vitamin D status on circulating sclerostin levels have been reported (5862). Furthermore, tumor necrosis factor alpha and Tnf-related weak inducer of apoptosis increase Sost expression (63).…”
Section: Sost/sclerostin Expression and Its Regulationmentioning
confidence: 99%
“…The results in men are consistent with those reported to occur in vitro , whereby treatment of osteogenic sarcoma SaOS2 cells with 1,25-dihydroxyvitamin D induced increases in both SOST mRNA and sclerostin protein levels [59]. In contrast to these results, however, are those in which 44 subjects with biochemically determined vitamin D deficiency (defined as a 25-hydroxyvitamin D level < 20 ng/mL) were treated with monthly intramuscular injection of 300,000 IU of vitamin D (cholecalciferol) and had a significant decline (−19.4%: P<0.01) in sclerostin levels [60]. Given the well-recognized inverse relationship between vitamin D and PTH, and the effects of PTH on sclerostin levels as described earlier in this review, it appears prudent at this time to interpret vitamin D dependent effects on sclerostin with caution.…”
Section: Hormonal Regulation Of Sclerostinmentioning
confidence: 99%